On a network SIS model with opinion dynamics - Xuan, W.; Ren, R.; Paré, P.E.; Ye, Mengbin; Ruf, S.; Liu, J. (2020)
This paper proposes a network continuous-time susceptible-infected-susceptible (SIS) model coupled with individual opinion dynamics, where the opinion dynamics models an individual's perceived severity of illness or perceived susceptibility. The effects of opinion dynamics on the network SIS model are studied by analyzing the limiting behaviors of the system model, equilibria of the system and their stability.